2017
DOI: 10.1007/s00018-017-2641-7
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor receptor beta identifies mesenchymal stem cells with enhanced engraftment to tissue injury and pro-angiogenic property

Abstract: Mesenchymal stem cells (MSCs) are heterogeneous likely consisting of subpopulations with various therapeutic potentials. Here we attempted to acquire a subset of MSCs with enhanced effect in wound healing. We found that human placental MSCs expressing platelet-derived growth factor (PDGF) receptor (PDGFR)-β exhibited greater proliferation rates and generated more colony-forming unit-fibroblast (CFU-F), compared to PDGFR-β MSCs. Notably, PDGFR-β MSCs expressed higher levels of pro-angiogenic factors such as Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 41 publications
0
43
0
1
Order By: Relevance
“…We also screened in vitro expanded MSCs for gene expression of several markers of MSCs that were identified previously either in bone (e.g., leptin receptor, Gremlin 1) [3,33], cartilage (e.g., Gremlin 1) [3], or muscle (e.g., PW1, CD56, ACTA2A) [1] regeneration or in wound healing (e.g., PDGFRB) [34]. The present study shows that LEPR is significantly lower in patients with OA compared to patients with OP and the controls in bonederived MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…We also screened in vitro expanded MSCs for gene expression of several markers of MSCs that were identified previously either in bone (e.g., leptin receptor, Gremlin 1) [3,33], cartilage (e.g., Gremlin 1) [3], or muscle (e.g., PW1, CD56, ACTA2A) [1] regeneration or in wound healing (e.g., PDGFRB) [34]. The present study shows that LEPR is significantly lower in patients with OA compared to patients with OP and the controls in bonederived MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diabetes mellitus (DM) often experience impaired wound healing, which leads to the formation of chronic ulcers. The underlying pathogenesis is primarily accounted for by a weakened immune system [1], insufficient angiogenesis [2], impaired proliferation and migration of keratinocytes and fibroblasts [3], and diminished production of healing-related growth factors such as vascular endothelial growth factor (VEGF) [4], insulin-like growth factor 1 (IGF-1) [5], transforming growth factor-beta (TGF-β) [6], and platelet-derived growth factor (PDGF) [7].…”
Section: Introductionmentioning
confidence: 99%
“…We investigated the expression of classical MSC markers (CD73, CD90, CD105) and also that of other markers described as "stemness/proliferative-linked" markers like CD49f, stage-specific human embryonic antigen-4 (SSEA4), CD24 and PDGFRβ [44][45][46][47]. We observed that the MSC phenotype was not affected by the [O 2 ] since the percentage of positive cells for the classical MSC markers was similar in both conditions ( Figure 4A).…”
Section: Differential Expression Of Membrane Markersmentioning
confidence: 94%
“…Among the different markers analyzed, CD49f and SSEA4 remained highly expressed under low [O 2 ] in comparison with ambient air. In contrast, PDGFRβ, which is enriched in human placental MSCs with elevated colony forming unit efficiency [45], was moderately expressed in SCAPs irrespective of cell growth conditions and the percentage of positive cells was rather decreased under low [O 2 ]. In addition, CD24 expression, which may refer to the number of committed progenitors cells in the papilla tissue, was not differentially expressed in our cell growth conditions [44].…”
Section: High Proliferative Capacity But Not Better Clonogenicity Undmentioning
confidence: 99%